A new efficient analytically proven lossless data compression for data transmission technique - Daud, Mohd Azlan; Kamel Ariffin, Muhammad Rezal (Institute for Mathematical Research, Universiti Putra Malaysia, 2013)
A new lossless data compression method for data transmission is proposed. This new compression mechanism does not face the problem of mapping elements from a domain which is much larger than its range. Our new algorithm sides steps this problem via a pre-defined code word list. The algorithm has fast encoding and decoding mechanism and is also proven analytically to be a lossless data compression technique.